Protonic cell performance employing electrolytes based on plasticized methylcellulose-potato starch-NH4NO3 - Hamsan, M.H. (2019)
Electrolytes consisting of methylcellulose/potato starch blend incorporated with ammonium nitrate (NH4NO3) are prepared by solution cast method. Field emission scanning electron microscopy (FESEM) discovers that methylcellulose and starch are miscible. Cation transference number (tcat) of the highest conducting electrolyte is discovered to be 0.40. Linear sweep voltammetry (LSV) show that the electrolyte is stable in the voltage range of 1.50 to 1.88Â V from 298 to 343Â K. Protonic conduction in the electrolyte has been further proven via cyclic voltammetry using both reversible Zn + ZnSO4Â·7H2O and blocking stainless steel electrodes. The open circuit voltage (Voc) of the protonic cell is lasted for 24Â h at 1.52Â V. The value of Voc is inversely proportional to the temperature. The maximum capacity, internal resistance, and power density of the protonic cell at 343Â K are found to be 42Â mAÂ h, 17Â Î©, and 13.5Â mWÂ cmâ2, respectively. Rechargeability of the protonic cell has been examined for 15Â cycles at different constant current. Â© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.